Knee Movement Characteristics of Basketball Players in Landing Tasks Before Onset of Patellar Tendinopathy: A Prospective Study - Feng, Ru; Best, Thomas M.; Wang, Lin; Gao, Weiwei; Liu, Hui; Yu, Bing (Frontiers in Sports and Active Living, 2022)
Background Patellar tendinopathy is one of the most common injuries for basketball players. Jumping and landing movement patterns are potential risk factors for patellar tendinopathy. Hypothesis Male college basketball players who developed patellar tendinopathy would demonstrate greater peak vertical ground reaction force and knee flexion angular velocity, and smaller knee flexion range of motion and knee flexion angles at initial contact compared to players who did not develop the injury when performing a stop-jump task within a year prior to the onset of the injury. Study Design Prospective study. Methods Freshmen college basketball male players (n = 181) were recruited for three consecutive years and followed to the end of the third year of the study. Three-dimensional kinematic and kinetic data during a stop-jump task were collected for all participants at the beginning of each school year. Peak vertical ground reaction force, knee flexion angle at initial foot contact with the ground, range of motion for knee flexion and maximal knee flexion angular velocity during the landing phases of the stop-jump task were collected and calculated. Development of patellar tendinopathy was monitored in follow-up. Independent t-tests and Cohen's d effect sizes (ES) were used to compare movement patterns between injury and no injury groups for each school year. Results A total of 60 knees developed patellar tendinopathy. The injury groups had a significantly greater peak vertical ground reaction force in freshmen and junior years (P = 0.020, ES = 0.13; P = 0.046, ES = 0.17), smaller knee flexion ROM in freshmen year (P = 0.002, ES = 0.10), and greater maximum knee flexion angular velocity in freshmen and junior year (P = 0.012, ES = 0.10; P = 0.001, ES = 0.35) during the horizontal landing phase before the takeoff of the jump compared to the no injury groups. The injury groups also had a significantly smaller knee flexion angle at initial contact during vertical landing phase after the takeoff of the jump in freshmen and junior years (P = 0.001, ES = 0.36; P = 0.001; ES = 0.37) during vertical landing phase. Conclusion Peak vertical ground reaction force, knee flexion angle at initial foot contact, knee flexion range of motion, and maximum knee flexion angular velocity are associated with patellar tendinopathy among male college basketball players in different school years.